Discrete Simulation, Spatial Modelling And Characterisation Of Certain Geophysical Phenomena. - Radhakrishnan, Palanikumar (2004)
The four distinct problems of geophysical interest addressed in this thesis entitled as "Discrete simulation, spatial modelling and characterisation of certain geophysical phenomena" include (a) analysis of basin topology and reconstruction (b) estimation of fractal dimension through morphological decomposition procedure (c) generation, extraction and characterisation of multiscal enetworks from Digital Elevation Models(DEMs) and (d)spatio-temporal analysia of flood plain channel network (FPCN) and ideal dunes. The techniques such as mathematical morphology , fractals, and non-linear concepts have been used to address these problems in an elegant manner.